Analisis Kapasitas Daya Gardu Traksi pada Kereta Rel Listrik - MISBAHUDIN, MOCHAMAD RAYSAL ALVANTRA; FAUZIAH, DINI (e-Proceeding FTI, 2024)
As the times progressed, the movement from one city to another was very fast. Therefore, we need a transportation that can facilitate people's daily activities, one of which is the Electric Rail Train or KRL. Electric Rail Train is a railway facility that has its own propulsion in the form of a traction motor mounted on each axle through a gear box on an MC train (motor car) using an electric power source. The parameters of the bearing capacity of the substation are measured based on the ratio of the maximum current load and headway load. The calculation results show the required capacity with a rectifier capacity of 2354.88 kW and a transformer capacity of 2943.54 kVA on all types of parameters. With the rectifier capacity used is 78% and the transformer is 86%. This causes the capacity of the rectifier and transformer to be unable to supply power for the operation of the Electric Rail Train. Abstrak Seiring berkembangnya zaman pergerakan dari satu kota ke kota yang lain sangatlah cepat. Oleh karena itu, diperlukan suatu transportasi yang dapat memudahkan aktifitas masyarakat setiap hari salah satunya yaitu Kereta Rel Listrik atau KRL. Kereta Rel Listrik adalah sarana perkeretaapian yang mempunyai penggerak sendiri berupa traksi motor yang dipasang pada setiap as roda melalui gear box pada kereta MC (motor car) menggunakan sumber tenaga listrik. Parameter kemampuan daya dukung gardu diukur berdasarkan perbandingan beban arus maksimum dan beban headway. Hasil perhitungan menunjukan kapasitas yang dibutuhkan dengan kapasitas rectifier 2354,88 kW dan kapasitas transformator 2943,54 kVA pada semua jenis paramater. Dengan kapasitas rectifier yang terpakai sebesar 78% dan transformator sebesar 86%. Hal ini menyababkan kapasitas rectifier dan transformator tidak mampu menyuplai daya untuk pengoprasian Kereta Rel Listrik.